Higher anti‐tumour efficacy of platinum(IV) complex LA‐12 is associated with its ability to bypass M‐phase entry block induced in oxaliplatin‐treated human colon cancer cells - Vondálová Blanářová, O. (Cell Prolif, 2013)
OBJECTIVES: Therapeutic potential of conventionally used platinum‐based drugs in treatment of colorectal tumours has been limited due to high incidence of tumour resistance to them and to their severe side effects. This evokes a search for more suitable anti‐cancer drugs. We have compared ability of oxaliplatin and a novel platinum(IV) complex, LA‐12, to modulate the cell cycle and induce apoptosis in human colon adenocarcinoma HCT116 wt and p53/p21 null cells, and have investigated molecular mechanisms involved. MATERIALS AND METHODS: Cell cycle‐related changes were analysed by flow cytometry (bromodeoxyuridine/propidium iodide staining, histone H3 phosphorylation). Apoptosis was detected using flow cytometry (assays monitoring caspase activity) and fluorescence microscopy (nuclear morphology). Changes in levels of genes/proteins involved in cell cycle and apoptosis regulation were examined by RT‐PCR and western blotting. RESULTS: Our results highlight the outstanding ability of LA‐12 to induce effective elimination of colon cancer cells independently of p53/p21, and in significantly lower doses compared to oxaliplatin. While oxaliplatin induced p53‐ and p21‐dependent G(2)‐phase arrest associated with downregulation of cyclin B1 and Cdk1, LA‐12 allowed cells to enter M‐phase of the cell cycle regardless of p53/p21 status. CONCLUSIONS: Higher malignant cell toxicity and ability to bypass cell cycle arrest important for the cell damage repair suggest LA‐12 to be a more effective candidate for elimination of colon tumours from a variety of genetic backgrounds, compared with oxaliplatin.